Histopathological and immunohistochemical (IHC) diagnosis of non-Hodgkin lymphoma (LNH) in a female canine - Losada, Martha (2020)
The clinical case of a 2-year-old female canine patient, French Poodle breed, who had presented three evident oestrous in a period of less than six months, according to the owner, is described. In the initial clinical examination, a patient with apoplexy signs was observed and in the examination of the genitourinary apparatus, abundant vaginal sero-bloody secretion was evident. The ultrasound study of the inguinal region reveals the presence of a non-specific rounded hyperechogenic structure with multiple oncogenic areas suggestive of pyometra. Cytology was performed by ultrasound-guided mass puncture that showed as a presumptive diagnosis of round cell neoplasia. An exploratory laparotomy is performed in which a mass of reddish colour in the cervix of 8 cm in diameter and 3 cm wide was evident. Histopathological study of the tumour mass sample gave a definitive diagnosis of malignant neoplasm of large cells consistent with intermediate grade non-Hodgkin lymphoma. The confrontation with CD3 biomarkers yielded a severe reactivity result with extensive multifocal distribution. Given the casuistic conditions, euthanasia was performed. The autopsy showed metastatic foci in the ribs.